Level of serum matrix metalloproteinase-9 in patients with acute coronary syndrome in Vietnam - Chí, Đỗ Hữu; Phương, Nguyễn Thị Minh; Huyền, Bùi Thị; Dũng, Nguyễn Tiến; Minh, Phạm Đình; Lợi, Đỗ Doãn; Huyền, Nguyễn Thúy; Nhi, Nguyễn Bích; Chi, Phan Văn; Thảo, Lê Thị Bích (Vietnam Journal of Biotechnology, 2018)
Acute Coronary Syndrome (ACS) is one of the foremost causes of mortality and morbidity worldwide as well as Vietnam. ACS was evoked by rupture or erosion of atherosclerotic plaques that was divided into Non–ST-segment elevation Acute Coronary Syndrome (NSTEACS) and ST-segment elevation myocardial infarction groups (STEMI). The matrix metalloproteinase (MMPs) is an enzyme family with fucntioning in the degradation of extracellular matrix and disruption of basement membranes. Of the MMPs, MMP-9 is expressed in the atherosclerotic plaques and plays a key role in the rupture of vulnerable atherosclerotic plaques. In this work, we measured the serum MMP-9 level in 205 patients with acute coronary syndrome (including 103 of NSTE-ACS and 102 of STEMI patients) and 101 healthy participants by sandwich Elisa method. The results showed that the MMP-9 level was significantly higher in NSTE-ACS and STEMI compared to the control group (208.59 ± 100.47 ng/mL, 189.98 ± 112.81 ng/mL vs 168.50 ± 79.52 ng/mL, respectively, P=0.014). However, a logistic regression analysis indicated that the MMP-9 level was only significantly higher in patients with NSTE ACS (OR= 1.0048, CI 95%= 1.000-1.009; P= 0.018). The serum MMP-9 level is correlated with traditional risk factors such as glucose, Cholesterol and Triglyceride by multiple logistic regression analysis. Conclusion: Our study suggests that the serum MMP-9 level is significantly associated with the NSTEACS and is a potential marker for dianogsis of ACS in the Vietnamese patients